ТЕХНОЛОГИЯ CLIL В ПРЕПОДАВАНИИ ОБЩЕОБРАЗОВАТЕЛЬНЫХ ДИСЦИПЛИН - Балаканова, А.Е. (My University, 2019)
Аннотация В данной статье приведены основные характеристики данной методики, обоснована целесообразность её использования на текущем этапе развития системы образования Республики Казахстан с учётом задач, поставленных Главой государства. Автор знакомит с некоторыми приемами методики CLIL (Content and Language Integrated Learning). Аbstract This article presents the main characteristics of this methodology, substantiates the expediency of its use at the current stage of development of the education system of the Republic of Kazakhstan, taking into account the tasks set by the Head of State. The author introduces some of the techniques of CLIL (Content and Language Integrated Learning).
CLIL technology in the teaching of general subjects
Keywords: CLIL технология; качество образования; компонент обновленного содержания образования; современные технологии; CLIL technology; quality of education; a component of the updated education content; modern technologies